1984
DOI: 10.1002/1097-0142(19841015)54:8<1734::aid-cncr2820540844>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure estimation in recipients of marrow transplants

Abstract: The resting metabolic expenditure of seven allogeneic marrow transplant patients supported by total parenteral nutrition was monitored by respiratory indirect calorimetry using a portable apparatus with a plexiglass canopy. The averaged measurements of resting metabolic expenditure using indirect calorimetry were highly correlated with calculated basal energy expenditures, ideal body weights, fat‐free weights, and actual body weights. No consistent correlation was demonstrated between resting metabolic expendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…Variations in measured REE during HSCT have previously been reported in adults and children 11-14 . In a group of 6 children undergoing autologous HSCT for malignant disease, mean REE was 111% of predicted BMR in those receiving PN before high dose chemotherapy conditioning, and 128% of predicted BMR in those receiving PN after conditioning 13 .…”
Section: Discussionmentioning
confidence: 75%
“…Variations in measured REE during HSCT have previously been reported in adults and children 11-14 . In a group of 6 children undergoing autologous HSCT for malignant disease, mean REE was 111% of predicted BMR in those receiving PN before high dose chemotherapy conditioning, and 128% of predicted BMR in those receiving PN after conditioning 13 .…”
Section: Discussionmentioning
confidence: 75%
“…Szeluga et al 4 reported that the energy requirements of the six children they studied increased during HSCT. Hutchinson et al 26 reported an average energy requirement 5% above that estimated by the Harris-Benedict equation, with individual patients' needs ranging from 79% to 121% of the estimate. Others report that individuals undergoing HSCT have energy requirements 1.3 to 1.5 times those obtained by using the Harris-Benedict equation.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to energy requirements, estimates are at around 130-150% (30-35 kcal/kg/day) of the basic theoretical energy expenditure [75,80,81]. The contribution of protein via the enteral route is estimated at about 0.2 g/kg unless the patient has a BMI of <30 kg/m 2 , in which case it must be reduced to 75%.…”
Section: Nutritional Indications During Mucositis Associated With Hemmentioning
confidence: 99%